Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 6 - Inverse Functions - 6.3* The Natural Exponential Function - 6.3* Exercises - Page 452: 9


$x=ln\frac{1}{\sqrt (e-1)}$

Work Step by Step

Given: $e-e^{-2x}=1$ $e-1=e^{-2x}$ $(-2x)lne=ln(e-1)$ This implies $x=ln\frac{1}{\sqrt (e-1)}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.